Dissipation, transfer and safety evaluation of emamectin benzoate in tea. (1st July 2016) - Zhou, Li; Luo, Fengjian; Zhang, Xinzhong; Jiang, Yaping; Lou, Zhengyun; Chen, Zongmao
Highlights: QuEChERS–UPLC–MS/MS method was developed for quantification with high sensitivity. Dissipation of emamectin benzoate and transfer from tea to brew were investigated. Health risk of emamectin benzoate in tea was evaluated based on RQ value. Abstract: The dissipation and residue of emamectin benzoate in tea leaves and the residue transfer from tea leaves to tea brew were investigated by modified QuEChERS (quick, easy, cheap, effective, rugged and safe) combined with ultra performance liquid chromatography tandem mass (UPLC–MS/MS). The average recoveries ranged 85.3–101.3% with relative standard deviation (RSD) less than 15%. The limits of quantification (LOQ) were 0.005 mg kg −1 in tea leaves and 0.0004 mg L −1 in brew. Emamectin benzoate dissipated rapidly in tea with half-life ( t 1/2 ) of 1.0–1.3 days. The terminal residues of emamectin benzoate were less than 0.062 mg kg −1 . The leaching rate of emamectin benzoate from freshly-made tea to brew was <5%. The risk of emamectin benzoate at the recommended dosage was negligible to humans depending on risk quotient (RQ) value, that was lower than 1 significantly. This study could provide guidance for the safe use of emamectin benzoate and serve as a reference for the establishment of maximum residue limits (MRLs) in China.